Malaria caused by Plasmodium vivax: recurrent, difficult to treat, disabling, and threatening to life--the infectious bite preempts these hazards. - Kevin Baird, J (2013)
The maxim 'an ounce of prevention is worth a pound of cure' finds few better demonstrations than with malaria caused by Plasmodium vivax. Thoroughly neglected over the past 60 years, the chemotherapy of this complex infection has been dangerous and ineffective until the present. Work is at last being done, but seeing that translate to real improvements at the periphery of care delivery will take years of deliberate effort. In the meantime, patients face substantial risk of debilitating, threatening, and fatal courses of illness associated with a diagnosis of vivax malaria. For some of the most vulnerable to such outcomes--pregnant women and infants--repeated attacks of acute vivax malaria from a single infectious anopheline bite is now not preventable. One of the few measures than can be immediately applied with rigor is vector control, thereby effectively preventing as many of these difficult and dangerous infections as possible. This commentary emphasizes the dire consequences of infection by P. vivax and the real difficulty of dealing with them. That, in turn, emphasizes the many benefits to be derived by preventing them in the first place.